Cubic negative stiffness lattice structure for energy absorption: Numerical and experimental studies. (1st December 2019) - Ha, Chan Soo; Lakes, Roderic S.; Plesha, Michael E.
Abstract: We present a new type of a truly three-dimensional cubic negative stiffness lattice structure that can achieve energy absorption and recover its original configuration under cyclic loading in excess of a strain of approximately 20%. This structure was composed of multiple unit cells exploiting negative stiffness from controlled elastic buckling. Structural properties were designed to be tuned by adjusting geometry. The effective Poisson's ratio was equal to zero regardless of the constituent material. Geometric parameters that can lead to the desired energy absorption without yielding the structure were determined by finite element analysis. We then fabricated samples representing the lattice structure with different sizes through additive manufacturing and performed cyclic loading experiments to capture stress-strain hysteresis loops. Results clearly showed that the designed structure was capable of absorbing mechanical energy effectively with a full recovery of geometry in three principal directions and that the amount of energy absorbed during cyclic loading increases with its size.